Cytotoxic alkaloids from leaves and twigs of Dasymaschalon sootepense - Sakchai Hongthong (2018)
Bioassay-guided fractionation of the cytotoxic ethyl acetate fraction of the sequential methanol extract from the leaves and twigs of Dasymaschalon sootepense led to the isolation of a new 7-hydroxy aporphine alkaloid, 6a,7-dehydrodasymachaline (1) along with the five known compounds (-)-nordicentrine (2), dicentrinone (3), (-)-sinactine (4), aristolactam AII (5) and epiberberine (6). Their structures were elucidated by spectroscopic methods. This is the first report of alkaloids 1-2 and 5-6 from the genus Dasymaschalon. Compounds 1 and 5 showed cytotoxicity against a panel of cancer cell lines.